Core-shell structured Co@NC@MoS2 magnetic hierarchical nanotubes: Preparation and microwave absorbing properties. (20th November 2022) - Zhang, Yunfei; Li, Yulong; Wei, Mengmeng; Yang, Dengtao; Zhang, Qiuyu; Zhang, Baoliang
Highlights: A novel Co@NC@MoS2 magnetic hierarchical nanotube is designed and prepared. The minimum reflection loss (RLmin ) exceeds −61.97 dB. The effective absorption bandwidth (EAB) covers 5.6 GHz. The electromagnetic parameters can be adjusted by changing the load of MoS2 . Abstract: In this study, a new lightweight one-dimensional absorber Co@NC@MoS2 was designed and prepared. Firstly, polydopamine (PDA) was coated by oxidative self-polymerization with cobalt-nitrilotriacetic acid chelate nanowires (Co-NTAC) as template. Then core-shell structured magnetic hierarchical nanotubes (Co@PDA@MoS2 ) were prepared by one-step hydrothermal method. After thermal annealing, PDA layer was transformed into nitrogen doped carbon layer (NC) to obtain the efficient microwave absorber Co@NC@MoS2 . The removal of template and growth of MoS2 were completed simultaneously, the preparation process was simplified. Because of its good magnetic loss and dielectric loss, Co@NC@MoS2 shows excellent microwave absorption performance. Under filler content of 15 wt.%, the minimum reflection loss (RLmin ) can reach -61.97 dB@9.2 GHz, and the effective absorption bandwidth (EAB) is 5.6 GHz. The electromagnetic parameters of Co@NC@MoS2 can be further adjusted by changing the load of MoS2 . Meanwhile, the structure and composition of Co@NC@MoS2 were systematically analyzed. The influence of the microstructure on the microwave absorbing properties was investigated, and the microwave attenuation mechanism is revealed. As an efficient and lightweight absorber, Co@NC@MoS2 has potential application value in the construction of new stealth coatings.